(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The study presented the landscape as a fundamental right, which influences human experiences and natural behaviors. From this context, it was discussed about forest fires as phenomena that cause landscape changes, leading to the transmutation of the ecological and cultural structuring of spaces. Nevertheless, using the hypothetical-deductive method and the review of the research by Nunes et al (2008), it was questioned about the quality of the landscape as an element to increase the risks of forest fires, in a bilateral perspective. That is, the objective was to demonstrate that the landscape is altered by fires in the same way that it can influence and / or indicate their occurrence. In this sense, the research is justified by the possibility of valuing the quality of the landscape as a tool for refining forest fire risk zoning maps. Finally, it was concluded that there is a relative correspondence between landscape quality and forest fire risks, as some biomes - such as the cerrado - have fire as a constituent element